Age and sex differences in ischemic stroke treatment in a nationwide analysis of 1.11 Million hospitalized cases - Weber, Ralph; Krogias, Christos; Eyding, Jens; Bartig, Dirk; Meves, Saskia H.; Katsanos, Aristeidis H.; Caso, Valeria; Hacke, Werner (Stroke, 2019)
Background and Purpose: To date, there is still uncertainty about age and sex differences in access to stroke unit treatment and use of intravenous thrombolysis (IVT), while age and sex differences have not been investigated for the new treatment option of mechanical thrombectomy (MT). We, therefore, undertook a complete nationwide analysis of all hospitalized ischemic stroke patients in Germany from 2013 to 2017. Methods-We used the nationwide administrative database of the German Federal Statistical Office and investigated access to stroke unit treatment, IVT, MT, and in-hospital mortality. Patients were subdivided into 6 predefined age groups (20-44, 45-59, 60-69, 70-79, 80-89, and >90 years). Pooled overall and age group estimates were calculated using the random-effects model. To evaluate potential sex disparities, we estimated odds ratios (ORs) with 95% CIs. Results-A total of 1112570 patients were hospitalized for first or recurrent ischemic stroke from 2013 to 2017. Overall, stroke unit treatment increased significantly from 66.8% in 2013 to 73.5% in 2017, as did IVT (from 12.4% to 15.9%) and MT (from 2.4% to 5.8%; all P<0.001). Although the difference became smaller over time, patients >= 80 years of age still received significantly less often treatments. Men of all age groups had a significantly higher probability receiving stroke unit treatment (OR, 1.11; 95% CI, 1.09-1.12) and lower in-hospital mortality (OR, 0.91; 95% CI, 0.89-0.93). No disparity was observed in the use of IVT (OR, 1.00; 95% CI, 0.98-1.01), while women of all ages were treated more often with MT (OR, 1.26; 95% CI, 1.22-1.30). Conclusions-Access to stroke unit treatment has to be increased in both older patients and women of all ages. While there was no sex difference in IVT use, it is important to further investigate the significantly higher frequency of MT in women with ischemic stroke irrespective of age.
Gesehen am 20.03.2020